Performance Analysis of Transmit Antenna Selection with MRC in MIMO for Image Transmission in Multipath Fading Channels Using Simulink - Vaibhav S Hendre; M Murugan; Sneha Kamthe (Institute of Advanced Engineering and Science, 2015)
Multiple antenna configurations can be used to increase the data throughput reducing the effects of multipath fading and interference when channel bandwidth is limited. Orthogonal Space Time Block Codes along with Transmit antenna selection can improve the performance of multiple input multiple output systems. In this paper, we present the Transmit Antenna Selection (TAS) technique based on the Maximal Ratio Combining (MRC) scheme with single antenna selection for image transmission. The performance analysis of the system was carried out under different fading channels i.e. Rayleigh and Rician channel for image input. We design end to end TAS/MRC system in Simulink with advancements in the channel designs and receive diversity techniques along with the feedback models. The Bit Error Rate (BER) analysis was performed for the combinations of number of transmit and receive antennas for TAS/MRC system for various fading environments.